Terapi Sel Punca untuk Penyakit Jantung - Vireza Pratama; Yoga Yuniadi (The Indonesian Heart Association, 2012)
Despite a lot of advancesin current therapeutic modalities, heart failure and coronary artery disease are still the leading cause of morbidity and mortality. Current management of heart failure indeed increase survival rate, however re-hospitalization and mortality rate remain high. Furthermore, none of those therapeutic modalitiesare based on myocardial regeneration concept.Stem cell therapy is an interesting new concept in heart failure management. Various cell types, administration route and cell expansions strategies are extensively studied. Stem cell improve myocardial perfusion and differentiate into angiogenic and contractile cell. Stem cell therapy is a promising regeneratif medicine in the future.